Multiple Coexisting Species and the First Known Case of a Cheater in Epicephala (Gracillariidae) Associated with a Species of Glochidion (Phyllanthaceae) in Tropical Asia. Issue 4 (25th August 2020) - Wang, Zhibo; Yang, Xiaofei; Zhang, Zhenguo; Shi, Fuchen; Li, Houhun
Abstract: Glochidion plants and Epicephala moths played different roles and kept the balance in the mutualism. We studied the four coexisting Epicephala species on Glochidion sphaerogynum in detail and reconstructed the phylogenic tree of 40 Gracillariidae species. The results showed that one of them ( Epicephala impolliniferens ) did not pollinate G. sphaerogynum, because of lacking the specialized structure of carrying pollen. These results suggested that E. impolliniferens acted as a 'cheater' in the system. The phylogenetic analyses suggested that E. impolliniferens derived from a pollinating species, and had secondarily gave up the ability to pollinate. This is a typical phenomenon of mutualism reversal. The phenomenon exhibits the co-evolutionary diversification under selection pressures.